Keragaman Karakter Morfologis Plasma Nutfah Spesies Padi Liar (Oryza spp.) - Tintin Suhartini (Buletin Plasma Nutfah, 2010)
Wild rice spesies is relativeof cultivated rice and has many differences of its characteristic.Morphological characteristic variation on crop can be used asworking assets in breeding program. Morphologicalcharacterisation was conducted in three planting seasons in2004 until 2005 at Indonesian Center for AgriculcuralBiotechnology Research and Development green houseconsisted of 88 accessions of 18 wild rice spesies whichbelonged to 4 groups of Oryza spp. (Oryza sativa, O.officinalis, O. meyeriana, and O. ridleyi). The characteristicobserved were include 12 quantitative characters and 5qualitative characters with 23 subcharacters. The wide ofquantitative morphological character variances were found inplant high, tiller number, days of flower, total number grain/panicle, awning length and stalk diameter, while the narrowcharacter variances were found in panicle length, 1.000 grainsweigth, grain shape, total internode and internode length. Thequalitative characters variance were found in grains, stalk,ligule and leaf morphology, while panicle morphology of wildrice species was dominated by open panicle type, erect panicle,secondary branching were absent and well exserted.